Growth and intestinal morphology in Nile tilapia (Oreochromis noloticus): decrease in fishmeal in diets with crude protein levels - Honorato, Claucia Aparecida; Souza, Rebeca Maria; Santos, Rudã Fernandes Brandão; Neu, Dacley Herts; Carneiro, Dalton José [UNESP] (Medicina Veterinaria (UFRPE), 2021)
The objective of this work was to evaluate the effect of the decrease of fishmeal in diets with crude protein levels on performance, nutrient retention efficiency, and intestinal histology in the Nile tilapia (Oreochromis niloticus). We used 180 tilapia fingerlings with an initial weight of 1.17 ± 0.05 g, distributed in 18 aquariums for 75 days. The results were analyzed in a completely randomized design, with six treatments in a 3x2 factorial, corresponding to three crude protein levels in the diets (20%, 24% and 28%) and two levels of inclusion of fishmeal-FP (25% or 50% of the protein level of the diet), with three replications. When the analysis of variance showed significant differences between treatments, the means were compared by the Tukey test. Production performance and nutrient retention efficiency and changes in histology and height of intestinal villi were evaluated. The increase in protein in the diet provided an increase in weight gain and the specific growth rate. Diets with protein levels of 28% promote nutrient balance to the point of decreasing the inclusion of fishmeal (25%), reflecting better productive performance indexes and adaptations in the morphology of the digestive tract of Nile tilapia. Histomorphometric changes are related to the diet provided and represent an adaptive response to metabolism. It was concluded that juvenile tilapia diets with 28% crude protein can decrease the inclusion of fishmeal (25%), reflecting better productive performance indexes and adaptations in digestive tract morphology.
Crescimento e alterações morfológicas no intestino de tilápia do Nilo (Oreochromis noloticus): diminuição da farinha de peixe em dietas com níveis de proteína bruta
Keywords: Fish nutrition; Histology; Protein sources